Campyloneuropsis cincticornis as a potential biological control agent of the South American tomato pinworm Phthorimaea absoluta: predation activity, oviposition and relationship with solanaceous host plants - Sola, Sofía A.; Rocca, Margarita; Salas Gervassio, Nadia G.; Peñalba, Julieta N.; Montiel Cáceres, Rocío I.; Luna, M. Gabriela (Frontiers in Agronomy, 2025)
Biological control is a key component of Integrated Pest Management (IPM) programs aimed at meeting yield and environmental goals of agriculture. In the search for effective natural enemies against the globally invasive tomato pest Phthorimaea absoluta, we evaluated the biological traits of the Neotropical mirid Campyloneuropsis cincticornis. Through laboratory bioassays, we assessed: (1) predation rates of different developmental stages of C. cincticornis on P. absoluta eggs and larvae; (2) oviposition behavior on two host plants—Solanum sisymbriifolium (sticky nightshade) and S. lycopersicum (tomato), and (3) development time on both plants. Older nymphs and adult females consumed more P. absoluta eggs and all stages (except first-instar nymphs) were able to feed on larvae, including those concealed inside leaf mines. Oviposition was markedly higher on S. sisymbriifolium, suggesting a strong preference likely shaped by offspring performance. C. cincticornis egg development time did not differ between host plants, whereas nymphal development was significantly faster on S. sisymbriifolium. These findings position C. cincticornis as a promising candidate for both augmentative and conservation biological control of P. absoluta, particularly in systems where native solanaceous vegetation is present.